Measuring journal diffusion using periodic citation counts - S.A., Sanni; A.N., Zainab; R.G., Raj; A., Abrizah; Sanni, S.A.; Zainab, A.N.; Raj, R.G.; Abrizah, A. (Malaysian Journal of Library and Information Science, 2017)
Sanni, S. A., Zainab, A. N., Raj, R. G., & Abrizah, A. (2014). Measuring journal diffusion using periodic citation counts. Malaysian Journal of Library & Information Science, Vol.19, no. 1: 23-36. This paper presents the relative percentile of diffusion (RPDiF) and compares it with the results of the following indicators: synchronous diffusion factor (DiF), synchronous relative diffusion factor (RDiF), and the five years impact factor (5IF) scores – to assess the influence of journals. The approach involves collection, analyses and comparison of bibliometric data for42 Malaysian journals that have garnered citations in the Web of Science (WoS) during 2006 to 2010.Findings show that it is important to read the RDiF with the RPDiF because RPDiF shows that journals with high RDiF and low RPDiF do not possess strong quality profile like those with both high RDiF and RPDiF. The paper concludes that a journal can be said to demonstrate high quality impact and influence if it achieves a high DiF, RPDiF and 5IF. This study contributes in providing an additional quality indicator to evaluate journals not indexed by mainstream citation databases.